Strategi Guru PAI dalam Proses Pembelajaran untuk Membentuk Karakter Disiplin Siswa Kelas VII di MTs Nusantara Sukolilo - Andrian Bintang; Saiful Bahri; Mahbub Junaidi (-, 2026)
This study aims to describe the strategies used by Islamic Religious Education teachers in the learning process to instill discipline in seventh-grade students at MTs Nusantara Sukolilo. The research method used was qualitative with a descriptive approach. Data were obtained through interviews, observation, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that Islamic Religious Education teachers apply five main strategies in forming students' disciplined character, namely: (1) habituation, such as performing congregational prayers, attending on time, and obeying school regulations; (2) role models, by consistently demonstrating disciplined behavior in daily life; (3) reward and punishment, through giving awards to disciplined students and educational punishment for those who break the rules; (4) supervision, in the form of teacher control over student behavior both inside and outside the classroom; and (5) motivation, through giving religious advice and encouragement so that students have an internal awareness to be disciplined. Supporting factors for implementing this strategy include sound lesson planning, school support, and parental involvement. Meanwhile, obstacles include negative peer influence, unsupportive family conditions, and low levels of discipline awareness among some students. Therefore, this study concludes that Islamic Religious Education (PAI) teacher strategies play a crucial role in developing students' disciplined character. However, for this strategy to be effective and sustainable, consistent teacher involvement and close collaboration between the school, parents, and the students' social environment are required.